Lipid accumulation product: A novel marker for gout and hyperuricemia - Dexian Xian; Wen Wang; Hui Li; Geran Song; Daozheng Xu; Fengjun Zhang; Zhe Wang; Wenchang Xu; Hongyan Meng; Min Peng (PLoS ONE, 2025)
Background and Aim Using cross-sectional data from the 2009-2018 National Health and Nutrition Examination Survey, the purpose of this study was to investigate the potential link between lipid accumulation product and gout/hyperuricemia Methods The data from 10,871 individuals who participated in the National Health and Nutrition Examination Survey spanning the years 2009–2018 were utilized for additional scrutiny. Participants self-reported gout and hyperuricemia as measured by laboratory test data, and other relevant variables and information for LAP were included. Multivariate logistic regression, restricted cubic spline and p-trend test were employed to determine the association between LAP and gout/hyperuricemia. Results The study included 10,871 adults. The prevalence of hyperuricemia and gout was 20.9% and 5.57%, respectively. Compared with the first quartile, the fourth quartile of lipid accumulation product was associated with a 271% higher risk of hyperuricemia (OR = 3.711, 95% CI 2.732–5.042, p < 0.001) in a fully adjusted model. A similar association was found between continuous increase in lipid accumulation product and hyperuricemia (OR = 2.441, 95%CI = 1.348–4.42, p = 0.005), with p trends showing both < 0.001. The RCS model suggests a significant non-linear relationship between lipid accumulation product and the risk of gout/hyperuricemia. There was an inverted U-shaped relationship between lipid accumulation product and gout/hyperuricemia. Conclusions This study confirmed that lipid accumulation product has a high potential to predict the risk of gout/hyperuricemia. These findings suggested that the adjustment of the degree of fat accumulation may be a potential way to prevent and control the onset of gout/hyperuricemia.